Comparison Between Indonesian and German Regional Autonomy in Relation to the Government System - Putu Riskita Karina Pramesti (Universitas Bali Dwipa, 2023)
The purpose of this study is to explain the comparison between the regional autonomy of Indonesia and Germany concerning the system of government adopted by the two countries. Regional autonomy in a country, both in Indonesia and in Germany, has the same goal, namely to give authority to regional governments in managing internal affairs in their respective regional domains. However, the differences in the government systems adopted by the two countries have resulted in differences in the structure and implementation of the regional autonomy system in the two countries. The theories used in discussing this research are the theory of federalism, the theory of decentralization, and the theory of constitutionalism. The research method used in this research is normative legal research, namely research that examines document studies using various secondary data such as court decisions, laws, and regulations, legal theory, and can be in the form of opinions of scholars. In addition, this study also uses the comparative legal research method, namely a research methodology conducted by comparing the legal systems of two or more different countries or jurisdictions. The comparison of the regional autonomy of Indonesia and Germany is related to the difference in the system of government adopted by the two countries where Indonesia has a government system called the Unitary State of the Republic of Indonesia (NKRI) while Germany has a federal government system called the Federal Republic of Germany (RFJ). This resulted in a different regional autonomy between Indonesia and Germany. In Indonesia, there are restrictions on local governments to regulate their internal affairs whereby the supreme power rests with the central government while the states in Germany have greater authority in managing their internal affairs